Changes in cerebral [18F]-FDG uptake induced by acute alcohol administration in a rat model of alcoholism - Gispert, Juan D.; Spanagel, Rainer (Behavioural brain research, 2017)
Several [18F]-FDG positron emission tomography (PET) studies in alcoholics have consistently reported decreases in overall brain glucose metabolism at rest and following acute alcohol administration. However, changes in cerebral glucose utilization associated with the transition to addiction are not well understood and require longitudinal translational imaging studies in animal models of alcoholism. Here, we studied brain glucose uptake in alcohol drinking rats in order to provide convergent evidence to what has previously been reported in human studies. Brain glucose metabolism was measured by [18F]-FDG microPET imaging in different male Wistar rat groups: short-term drinking (three months), long-term drinking (twelve months) and alcohol-naïve. Global and regional cerebral glucose uptake was measured at rest and following acute alcohol administration. We showed that alcohol significantly reduced the whole-brain glucose metabolism. This effect was most pronounced in the parietal cortex and cerebellum. Alcohol-induced decreases in brain [18F]-FDG uptake was most apparent in alcohol-naïve rats, less intense in short-term drinkers and absent in long-term drinkers. The latter finding indicates the occurrence of tolerance to the intoxicating effects of alcohol in long-term drinking individuals. In contrast, some regions, like the ventral striatum and entorhinal cortex, showed enhanced metabolic activity, an effect that did not undergo tolerance during long-term alcohol consumption. Our findings are comparable to those described in human studies using the same methodology. We conclude that [18F]-FDG PET studies in rat models of alcoholism provide good translation and can be used for future longitudinal studies investigating alterations in brain function during different stages of the addiction cycle.